2004
DOI: 10.1016/j.cell.2004.11.047
|View full text |Cite
|
Sign up to set email alerts
|

TOR Regulates Ribosomal Protein Gene Expression via PKA and the Forkhead Transcription Factor FHL1

Abstract: The regulation of ribosome biogenesis in response to environmental conditions is a key aspect of cell growth control. Ribosomal protein (RP) genes are regulated by the nutrient-sensitive, conserved target of rapamycin (TOR) signaling pathway. TOR controls the subcellular localization of protein kinase A (PKA) and the PKA-regulated kinase YAK1. However, the target transcription factor(s) of the TOR-PKA pathway are unknown. We show that regulation of RP gene transcription via TOR and PKA in yeast involves the Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
456
4
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 430 publications
(491 citation statements)
references
References 47 publications
18
456
4
2
Order By: Relevance
“…For the RP genes, Rap1 together with the Fhl1-Ifh1 complex is the main transcriptional regulator (Klein & Struhl, 1994;Martin et al, 2004;Rudra et al, 2005). The activity of all these factors is regulated via partially overlapping pathways (involving TOR and PKA), allowing a coordinate expression of all the components required for ribosome biosynthesis.…”
Section: Discussion Continuous Cultures: Subsiding Growth Rate Effectsmentioning
confidence: 99%
“…For the RP genes, Rap1 together with the Fhl1-Ifh1 complex is the main transcriptional regulator (Klein & Struhl, 1994;Martin et al, 2004;Rudra et al, 2005). The activity of all these factors is regulated via partially overlapping pathways (involving TOR and PKA), allowing a coordinate expression of all the components required for ribosome biosynthesis.…”
Section: Discussion Continuous Cultures: Subsiding Growth Rate Effectsmentioning
confidence: 99%
“…Concerning the regulation of RP gene transcription by RNA polymerase II, it was found that TORC1 promotes complex formation between Fhl1, a forkhead-like transcription factor that binds to the promoter of RP genes, and its co-activator Ifh1 (Lee et al 2002;Martin et al 2004;Schawalder et al 2004;Wade et al 2004;Rudra et al 2005). This Fhl1-Ifh1 complex then promotes the expression of RP genes.…”
Section: Rapamycin-sensitive Signalling Via Torc1mentioning
confidence: 99%
“…While the utilization of metabolites such as sugars and lipids could be easily seen to be subject to differential regulatory pressures based on the metabolic niche of the organism, the expression of ribosomal protein genes is a highly conserved and universal process, and thus it is remarkable that the regulatory circuits controlling this process have been fundamentally rewired between S. cerevisiae and C. albicans.I nS. cerevisiae the regulatory circuit controlling the expression of ribosomal proteins consists of the generalist myb-domain containing transcription factor Rap1p together with the high-mobility group protein Hmo1p and a condition-sensitive switch complex made up of Ifh1 and Fhl1 [47][48][49][50][51]. In C. albicans, the Ifh1/Fhl1 switch appears to be conserved, but the key DNA-binding element of the circuit is the myb-domain protein Tbf1 ( [22 ] Lavoie et al, submitted) ( Figure 2c).…”
Section: Ribosomal Proteins and Ribosome Biogenesismentioning
confidence: 99%